1973
DOI: 10.1126/science.179.4071.377
|View full text |Cite
|
Sign up to set email alerts
|

Red Sea Drillings

Abstract: Recent drilling in the Red Sea has shown that much of the basin is underlain by evaporites of a similar age to that of evaporites found in the Mediterranean Sea. These evaporites and their structural positions indicate that other brine areas are present-and, indeed, several others have been discovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Previous publications (Coleman andothers, 1977, 1979) have shown that the dike swarms, gabbros, and continental dikes have definite tholeiitic affinities.…”
Section: Major Elementsmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous publications (Coleman andothers, 1977, 1979) have shown that the dike swarms, gabbros, and continental dikes have definite tholeiitic affinities.…”
Section: Major Elementsmentioning
confidence: 83%
“…recalculated using K-Ar age determinations A general synthesis of the harrats was made by Brown (1972) during his work on the tectonic map of Saudi Arabia. In the southern Shield, Coleman andothers (1977, 1979) concentrated on Harrat al Birk and Harrat as Sirat as well as the Tihamat 'Asir complex.…”
Section: Introductionmentioning
confidence: 99%
“…These reports have stimulated investigations into other hot brines which might provide evidence on this extraordinarily interesting point. We have examined material derived from hot springs at the bottom of the Red Sea (Atlantis-II) [3][4][5] which may be anticipated to have a similar geologic origin as the samples derived from the Cheleken Penninsula. We have examined in a neutron-multiplicity counter several kilograms of dry precipitate gathered from the Atlantis II site, which are relatively rich in some of the more volatile heavy elements.…”
mentioning
confidence: 99%
“…Seismic profiles from the hot brine area (Ross et al, 1969;Ross et al, 1973;Geophysical Appendix, this volume) show a coincidence in the depth of reflector S (the top of the evaporite sequence) and the level of the brine. If this coincidence is significant, it suggests that wherever the evaporites crop out in a closed depression, a brine pool is possible.…”
Section: Discussionmentioning
confidence: 95%